2014
DOI: 10.1590/0101-60830000000008
|View full text |Cite
|
Sign up to set email alerts
|

The current practices of intervention with batterers

Abstract: Background: Since the 70s there was a proliferation of intervention programs for batterers; however the results remain controversial. Objectives: This study aims to analyse the literature published between the years of 2000 and 2013 about the effectiveness of the intervention with batterers. Methods: A review of papers about intervention with batterers published during this period (2000-2013) was conducted. Social sciences databases were checked. Papers about programs for a specific public or programs with a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
(87 reference statements)
0
5
0
1
Order By: Relevance
“…In general terms, the main aim of these types of interventions is to reduce IPV risk factors and increase protective factors, which in turn prevent violence against their partners in current and future relationships (Bowen, ; Ferrer‐Perez, Ferreiro‐Basurto, Navarro‐Guzmán, & Bosch‐Fiol, ; Gondolf, ). However, these conclusions vary greatly from one study to another, depending on the study design or the source of information on recidivism (victim's report or official report) (Arbach & Bobbio, ; Babcock et al ., ; Cunha & Gonçalves, ; Lila, Gracia, & Catalá‐Miñana, ; López‐Ossorio et al ., ). Hence, it is difficult to precisely determine the degree of success of IPV intervention programmes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general terms, the main aim of these types of interventions is to reduce IPV risk factors and increase protective factors, which in turn prevent violence against their partners in current and future relationships (Bowen, ; Ferrer‐Perez, Ferreiro‐Basurto, Navarro‐Guzmán, & Bosch‐Fiol, ; Gondolf, ). However, these conclusions vary greatly from one study to another, depending on the study design or the source of information on recidivism (victim's report or official report) (Arbach & Bobbio, ; Babcock et al ., ; Cunha & Gonçalves, ; Lila, Gracia, & Catalá‐Miñana, ; López‐Ossorio et al ., ). Hence, it is difficult to precisely determine the degree of success of IPV intervention programmes.…”
Section: Introductionmentioning
confidence: 99%
“…Results are inconclusive about the effectiveness of intervention programmes for intimate partner violence (IPV) perpetrators (Arias, Arce, & Vilariño, 2013;Babcock, Green, & Robie, 2004;Cunha & Gonc ßalves, 2014;Eckhardt et al, 2013;Feder & Wilson, 2005;Pinto et al, 2010). In general terms, the main aim of these types of interventions is to reduce IPV risk factors and increase protective factors, which in turn prevent violence against their partners in current and future relationships (Bowen, 2011;Ferrer-Perez, Ferreiro-Basurto, Navarro-Guzm an, & Bosch-Fiol, 2016;Gondolf, 2004).…”
mentioning
confidence: 99%
“…Despite the diversity of outcomes, evaluation research is largely focused on behavior (Bowen, 2011). Recidivism or re-assault rates are the most common index used to assess post-intervention behavior (Cluss & Bodea, 2011; Cunha & Gonçalves, 2014a). This outcome measure is typically obtained through the victim and/or perpetrator self-report, official records/police data, and attrition analysis (Cluss & Bodea, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Research has consistently shown that one of the main problems of BIPs is the high rates of dropout (e.g., Cunha & Gonçalves, 2014;Jewell & Wormith, 2010), which justify the growing concern with this phenomenon and raise serious questions regarding these intervention programs (Ferrer-Perez & Bosch-Fiol, 2016). The non-completion of programs designed to reduce recidivism is considered a significant obstacle for treatment success (e.g., McMurran et al, 2010), having potentially severe implications for client welfare and public safety (Olver et al, 2011): first, dropout is a predictor of IPV re-assault (e.g., Bennett et al, 2007;Carney et al, 2006;Gondolf, 2000;Lauch et al, 2007;Lila et al, 2019;Olver et al, 2011); second, many variables that predict treatment dropout also predict IPV recidivism (e.g., Cattaneo & Goodman, 2005;Hanson & Wallace-Capretta, 2004;Stith et al, 2004) as well as general recidivism (e.g., Eisenberg et al, 2019;Gendreau et al, 1996).…”
Section: Introductionmentioning
confidence: 99%